Artificial Intelligence in Arabic Language Education: A Conceptual Review of Trends, Applications, Challenges, and Future Research in the Era of Generative AI. - Riski Gunawan (Al-Wazan: Journal of Arabic Education, 2026)
Artificial Intelligence (AI) has rapidly transformed educational practices by enabling personalized learning, intelligent tutoring, adaptive assessment, and automated feedback. The emergence of Generative AI, particularly Large Language Models such as ChatGPT, Gemini, Claude, and Microsoft Copilot, has further accelerated innovation in language education. While AI has been extensively adopted in English language learning, its application in Arabic language education remains relatively underexplored despite the unique linguistic characteristics and pedagogical demands of the Arabic language. This conceptual review examines recent developments in AI-assisted Arabic language education by synthesizing current knowledge on technological trends, pedagogical applications, implementation challenges, and future research directions. The review discusses how AI supports vocabulary acquisition, grammar instruction, listening, speaking, reading, writing, assessment, and teacher professional practice. Furthermore, the article highlights ethical concerns, institutional readiness, teacher competence, and digital equity as essential considerations for sustainable AI implementation. Based on the reviewed literature, this article proposes the Artificial Intelligence for Arabic Language Education and Pedagogy (AIALEP) Framework, which conceptualizes AI integration through six interconnected dimensions: educational theories, AI technologies, pedagogical functions, Arabic language skills, learning outcomes, and educational impact. The framework offers a comprehensive perspective for researchers, educators, curriculum developers, and policymakers seeking to integrate AI into Arabic language education responsibly and effectively.